Population Ecology and Possible Threats to Defassa Waterbuck (Kobus Ellipsiprymnus Defassa) in the Nechsar National Park, Ethiopia - Demisse, Birtukan Tsegaye; Deng, Gatriay Tut (International Journal of Zoology, 2022)
Because of potential conflicts with humans, we investigated the population structure of waterbuck (Kobus ellipsiprymnus defassa) in the Nechsar National Park, Ethiopia, from November 2019 to August 2020, using line transect methods. The estimated population was 118 and 104 in the wet and dry seasons, respectively, and averaged 111 (+8) or 0.23/km2. The proportion of each age group averaged 31% adult males, 45% adult females, 12% subadult males, 11% subadult females, and 2% juveniles; the large number of female individuals suggests a healthy and increasing waterbuck population. The distribution of waterbuck sightings among habitat types differed by season (χ2 = 15.97, df = 3, p<0.05). Different conservation measures should be taken to create a conducive environment for waterbuck and large park biodiversity.